Is technology change good for cotton farmers? A local-economy analysis from the Tanzania Lake Zone. (18th September 2017) - Gupta, Anubhab; Kagin, Justin; Taylor, J Edward; Filipski, Mateusz; Hlanze, Lindi; Foster, James
Abstract: Technological change holds the potential to increase crop output as well as incomes of farmers and the communities in which they live. We carry out a local economy-wide impact evaluation of productivity-enhancing technological change amongst small-scale cotton producers in Tanzania's Lake Zone. Our analysis reveals that demand constraints shift benefits from farmers to downstream processors, while limiting positive spillovers within local economies. Excess cotton gin capacity does the opposite. Interventions to ensure markets for increased output should complement strategies to raise productivity if a project's goal is to improve welfare in farm households and the communities in which they live.